Common bean (Phaseolus vulgaris L.) genotypes with resistance to BGYMV in Cuba - Morales-Soto, Arianna (2022)
Introduction. The Bean Golden Yellow Mosaic Virus (BGYMV) is one of the factors that limit the production of beans (Phaseolus vulgaris L.) in Cuba. Genetic improvement for resistance to this virus is one of the most effective strategies for disease control. Objective. To select common bean genotypes with resistance to BGYMV and grain yield stability. Materials and methods. Twenty-two bean genotypes (sixteen advanced lines donated by the Agricultural School of Zamorano, Honduras, the cultivar commercial ‘Cuba Cueto 25-9N’, the resistant and susceptible controls ‘Delicia 364’ and ‘Velasco Largo’, respectively). The presence of the bgm-1 gene, which confers resistance to BGYMV, was then identified from the presence of the SCAR SR2 marker. Results. The evaluation of the reaction in the field allowed the identification of nineteen genotypes with a resistant response to the natural infection of BGYMV. Sixteen common bean genotypes were identified with the presence of the SCAR SR2 marker and seventeen genotypes that showed stable grain yield behavior during the evaluation seasons, which may be useful for the genetic improvement of bean crops. Conclusion. The results allowed the identification of nineteen genotypes with resistance to BGYMV. The seventeen BGYMV-resistant with the SCAR SR2 marker and stable genotypes, could be included in the bean germplasm bank and as parents in crossing programs, as well as in regional yield trials in other bean-growing environments.